Local government shared services centers : management and organization (Emerald points., 2020)
Shared Service Centers (SSCs) support the management of administratively complex enterprises. Originating in the private sector, SSCs have increasingly been adopted in the public sector in an effort to reduce administrative costs, improve the quality of public services, reduce the risk of management error and make better use of human resources. The first book to thoroughly examine the organization, development and effectiveness of the shared service market in local governments across Poland, this study explores the process of creating SSCs, the key elements of unit management, the barriers and threats to both the creation and operation of SSCs, and the strategic technological solutions that local governments have utilized in shared service provision. The author argues that the implementation of SSCs represents the initial stage on the way to improving the effectiveness of public and local government administration, while stressing that further organizational changes and standardization processes are needed to achieve greater effectiveness, in a conclusion which makes essential reading for both practitioners in local government and scholars across the fields of public management, administration and economics.